Yolk sac tumour in pre-pubertal girl: a case report - Thirunavukkarasu, Ramanidevi; Lakshminarayanan, Balaji; Kumar, Prasannakumar Senthil; Hameed, Rifana Parveen Abdul; Kumar, Deepika Anand; Duraisamy, Sangavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The commonest malignant ovarian tumour in the adolescent group is yolk sac tumour. It is commonly encountered in adolescents and young women. Incidence is 1% of all ovarian tumours. We reported a case of yolk sac tumour in a 9-year-old girl who presented with intermittent lower abdominal pain, not settling with medical management. Abdominal ultrasonogram showed a left adnexal echogenic mass measuring 5×6 cm with cystic spaces and internal vascularity. MRI abdomen showed T2/STIR hetero intense mass indenting the uterus and posterior bladder wall, multiple bilateral internal iliac, external iliac, left common iliac, aortic and bilateral inguinal nodes along with minimal ascites were seen. She underwent laparoscopy with trucut biopsy which showed moderate nuclear atypia with occasional Schiller-Duval body. Medical oncologist opinion was obtained and she was advised 4 cycles of chemotherapy with carboplatin, bleomycin and etoposide. Later she was planned for laparoscopic cytoreductive surgery. Laparoscopy showed rudimentary uterus, residual left ovarian mass, bilateral normal tubes and small pre-pubertal right ovary. Hence, left salpingo-oophorectomy, infra colic omentectomy and suspicious residual deposits of 1×1 cm near the right broad ligament were removed. Histopathological report of ovary showed no evidence of any residual malignancy. Peritoneum and omentum were free of tumour. Following laparoscopic cytoreductive surgery she is on follow up with AFP till date which is in declining levels and almost reached a normal value.